Analysis of eating behaviors and eating habits, body mass index and waist-to-hip ratio in association with spirometry results of young adults - Dzięciołowska-Baran Edyta (Anthropological Review, 2017)
Behavior and eating habits stands as an important factor in terms of maintaining a good health condition in every age group. This involves optimal digestion, maintaining proper metabolism of the entire organism and thus maintaining proper body weight. It is especially important for students, as the increased mental activity results in increased energy expenditure. The state of body weight can affect the respiratory efficiency measured in spirometry. The aim of the study was to assessthe relation between behavior and eating habits, body mass index (BMI), waist-to-hip ratio (WHR) and results from spirometry tests among young adults.